Ten years follow-up under atorvastatin therapy of patients with carotid artery stenosis: the prognostic impact of oxidised low-density lipoprotein on carotid plaque progression and restenosis. : Atorvastatin and oxidized LDL in carotid artery stenosis - Polydorou, Adamantia; Alexopoulos, Konstantinos; Polydorou, Victoria; Skopelitis, Elias; Κougiali, Xanthula; Liasis, Nikolaos; Demesticha, Theano; Piagkou, Maria; Protogerou, Vasilios; Filippou, Dimitris; Velissariou, Eleni; Dimakopulos, George; et al. (Journal of Humanitarian Cardiovascular Medicine, 2022)
Background: Atorvastatin reduces oxidized low-density lipoprotein (oxLDL) levels and reduces the rate of plaque progression in patients with and without prior carotid angioplasty. The aim of our study was to investigate the durability of this effect and to explore possible prognostic impact of oxLDL levels on carotid stenosis and plaque stability. Methods: 106 patients (71 males, mean age 64.82±7.26 years) were studied. They were divided into two groups. Group 1 including patients with carotid stenosis >70% (n=50) who underwent carotid angioplasty prior to enrolment. Group 2 included those with <70% stenosis who were treated medically and were given atorvastatin with dose adjusted to maintain LDL cholesterol <100mg/dl. Anthropometrics, complete lipid profile, oxLDL and ultrasonography were performed at baseline, 1, 3, 6, 12 months and yearly thereafter for 10 years. Results: oxLDL levels significantly decreased from 53.3±10.91 mg/dl at baseline to 8.31±2.08 mg/dl at 12 months (p<0.001) and remained stable until the 10th year. In group 1, restenosis (>70%) was noticed in four patients, yet no further intervention was needed due to plaque morphology (echo-grade IV). In group 2, carotid stenosis was initially reduced (6th month – 4th year) and later relapsed (5th – 10th year), yet plaque morphology was recorded as type III or IV in almost all patients of group 2 (53=95%), indicating a significantly lower risk for stroke. Conclusion: Atorvastatin treatment to a target of LDL <100 mg/dl in patients with carotid stenosis is associated with marked and durable reduction of lipid levels, especially oxLDL and LDL and reduction in the rate of stenosis progression, improved plaque stability and decreased stroke risk.